Solution of Fractional Differential Equations Utilizing Symmetric Contraction - Aftab Hussain (Journal of Mathematics)
The aim of this paper is to present another family of fractional symmetric α-η-contractions and build up some new results for such contraction in the context of ℱ-metric space. The author derives some results for Suzuki-type contractions and orbitally T-complete and orbitally continuous mappings in ℱ-metric spaces. The inspiration of this paper is to observe the solution of fractional-order differential equation with one of the boundary conditions using fixed-point technique in ℱ-metric space.